Extracellular Nucleosomes Accelerate Microglial Inflammation via C-Type Lectin Receptor 2D and Toll-Like Receptor 9 in mPFC of Mice With Chronic Stress - Wu, Huanghui; Bao, Han; Liu, Cong; Zhang, Qiao; Huang, Ailing; Quan, Minxue; Li, Chunhui; Xiong, Ying; Chen, Guozhong; Hou, Lichao (Frontiers in Immunology, 2022)
Damage-associated molecular patterns (DAMPs) are the primary promoter of progressive neuroinflammation and are associated with chronic stress-related emotional disorders. The present study investigated the role and mechanism of extracellular nucleosomes and histones, the newly defined DAMPs, in mice with chronic stress. C57BL/6 mice were exposed to chronic unpredictable mild stress (CUMS) and corticosterone drinking, respectively, for 4 weeks. Negative emotional behaviors were comprehensively investigated. Microglial morphology, oxidative stress, and inflammation, as well as C-type lectin receptor 2D (Clec2d) and Toll-like receptor 9 (TLR9) expression in medial prefrontal cortex (mPFC) were assessed with flow cytometer and cell sorting. Specifically, microglial pro-inflammatory activation and inflammation were further investigated with stereotactic injection of recombinant nucleosomes and histones in mPFC and further evaluated with AAV-Clec2d knocking-down, DNase I, and activated protein C (APC) pretreatment. Moreover, the rescue effect by AAV-Clec2d knocking-down was observed in mice with chronic stress. Mice with chronic stress were presented as obviously depressive- and anxiety-like behaviors and accompanied with significant microglial oxidative stress and inflammation, indicating by reactive oxygen species (ROS) production, primed nuclear factor-κB (NF-κB) signaling pathway, activated NACHT, LRR, and PYD domain–containing protein 3 (NLRP3) inflammasome, and upregulated Clec2d and TLR9 in mPFC, together with histones dictation in cerebrospinal fluid and extracellular trap formation. Stereotactic injection of nucleosomes was contributed to promote microglial inflammation rather than histones in mPFC, indicating that the pro-inflammatory role was derived from extracellular histones-bound DNA but not freely histones. AAV-Clec2d knocking-down, DNase I, and APC were all effective to inhibit nucleosome-induced microglial oxidative stress and inflammation. Moreover, AAV-Clec2d knocking-down in mice with chronic stress exhibited reduced microglial inflammation and improved negative emotional behaviors. Our findings reveal a novel mechanism of DAMP-associated inflammation that extracellular nucleosomes accelerate microglial inflammation via Clec2d and TLR9, and then contribute to chronic stress-induced emotional disorders.